KESALAHAN JAWABAN TES TRIGONOMETRI MAHASISWA PENDIDIKAN MATEMATIKA SEMESTER PERTAMA - Anton Jaelani (AlphaMath : Journal of Mathematics Education, 2017)
Trigonometry was one of the basic topic used for learning advance mathematics. Lecturer borteacher and students often faced difficulties when they learned trigonometri and answeredtrigonometric exercises, moreover when they solved trigonometric problem. This articledescribed the undergraduate students unnecessary mistakes of trigonometric exercises. Theconjectures of mistakes was created based on students mistakes in learning trigonometry. Datacollection conducted from students test result. Data reduction, data display, and conclusiondrawing was used to analyze the data. Test result choosed analyzed based on the conjecturescreated. Research found nine students unnecessary mistakes of the trigonometric exerciseanswer agreed with the conjectures. These were student uncared place of quadrant, studentsgot accidently exchange formula, students created table to help them drawing trigonometricfunction graph, students drew trigonometric function graph in a straight line manner, studentsdid not add period in solution of trigonometric equation, students did not operate to all of thepart of equation, students applied distribution in a wrong place, students applied uncorrectformula, students did not connect between trigonometry other concept in mathematics.Keyword: Trigonometry, Unnecessary Mistake, Students Answer.